IDENTIFIKASI KESIAPAN DESTINASI WISATA SEKITAR TAMAN HUTAN RAYA WAN ABDURACHMAN (TAHURA WAR) MENUJU DESA WISATA BERBASIS SMART TOURISM - Rahayu Sulistiowati; Meiliyana; Dewie Brima Atika; Dimas Adi Saputra (Administratio, 2023)
This study aims to identify the readiness of tourism villages around the Taman Hutan Raya WAR to adopt the concept of Smart Tourism. The conceptual framework used in this research is based on the concept of Smart Tourism, which includes the use of information and communication technology (ICT) in managing tourist destinations. The research method used is qualitative research with a descriptive type. The study was conducted in Sumberagung Village, Kemiling District, Bandarlampung, and covered seven tourist destinations, namely Kampung Vietnam, Puncak Vietnam, Lembah Vietnam, Jukung Vietnam, Rusa Breeding, Lengkung Langit 2, and Gerbang Alam. The data collection process was carried out using observation and structured interviews. The data were analyzed using qualitative analysis techniques, namely content analysis. The results of the study indicate that tourism villages around Taman Hutan Raya WAR still need a lot of improvement in terms of infrastructure, services, and the implementation of information technology. However, they have great potential to develop Smart Tourism as one of the strategies to enhance the attractiveness of tourist destinations in the area. Therefore, this study provides an important theoretical contribution to the development of the concept of Smart Tourism in tourism village areas, as well as recommendations for stakeholders in developing the area.